Influence of Competitive Match Play on Countermovement Jump Performance, Lower-Limb Isometric Strength, and Self-Reported Subjective Measures 40 hours Postmatch in Professional Soccer. - Mukandi, Irvin; Bishop, Chris; Turner, Anthony; Beato, Marco (Journal of Strength & Conditioning Research, 2026)
Mukandi, I. Influence of competitive match play on countermovement jump performance, lower-limb isometric strength, and self-reported subjective measures 40 hours postmatch in professional soccer. J Strength Cond Res 40(2): 206–217, 2026—This study investigated the impact of competitive match play on countermovement jump (CMJ) performance, hamstrings and adductor isometric strength, and subjective self-reported measures 40 hours postcompetitive match play in professional soccer players. Twenty-eight professional players completed baseline assessments during preseason. Assessment 40 hours postmatch was limited to players who played ≥60 minutes, with players grouped into 2 categories based on minutes played: 60–89 minutes or 90–110 minutes. Baseline measures for subjective self-reported measures were collected 24 hours before each match. Across both groups, significant reductions (p < 0.05) were observed in all outcome, ratio, and driver metrics except for eccentric mean force. All strategy metrics significantly increased (p < 0.05). Minutes played and match demands were not significantly associated with CMJ performance (τb = −0.07 to 0.16 and τb = −0.28 to 0.00, respectively). Prone isometric 0° showed nonsignificant reductions (p > 0.05) in both conditions with trivial to small effects. Significant reductions (p < 0.05) were observed for both conditions for the supine 90° hamstring test, however minutes played, and match demands were not significantly associated with a reduction in performance (τb = −0.04 to −0.01 and τb = −0.27 to 0.21). Short lever hip adduction results showed nonsignificant reductions (p > 0.05) in the 60–89 minutes group, but significant decreases (p < 0.001) were observed for the dominant limb, nondominant limb, and total score in the 90–110 minutes condition. However, minutes played and match demands were not significantly associated with reduction in adductor isometric strength (τb = 0.18–0.22 and τb = −0.15 to 0.11). Subjective measures revealed significant reductions in sleep quality (p < 0.05) and composite scores (p < 0.001), and significant increases in muscle soreness (p < 0.001) across both conditions. Mood was only significantly reduced (p < 0.05) in the 90–110 minutes condition. No significant associations were found between minutes played, match demand, and self-reported subjective scores (τb = −0.07 to 0.05 and τb = −0.09 to 0.00).